2015
DOI: 10.1177/2040206615595318
|View full text |Cite
|
Sign up to set email alerts
|

A two-week regimen of high-dose integrase inhibitors does not cause nephrotoxicity in mice

Abstract: Background: The integrase inhibitors, raltegravir and dolutegravir, are nucleoside reverse transcriptase inhibitor-sparing agents which may be used as part of first-line antiretroviral therapy for HIV. These drugs inhibit creatinine secretion through organic cation transporters, thus elevating serum creatinine without affecting glomerular filtration. We sought to determine whether subtle signs of nephrotoxicity could be observed in mice administered a two-week regimen of highdose integrase inhibitors. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Females were then separated from males and housed in groups of up to four in individually ventilated cages (GM500, Tecniplast, Italy) in environmentally controlled rooms with a twelve-hour light-dark cycle. At E6.5, female mice received new drinking water mixed with dolutegravir (GSK-1349572A; AmBeed, Arlington Heights, Illinois, USA) in 0, 3.5 mg/l, 17.5 mg/l, or 35 mg/l concentrations to achieve 1×, 5×, or 10× clinical concentrations of DTG in serum [14]. Water and DTG-water consumption did not vary between groups and was approximately 5.45 ml/mouse per day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Females were then separated from males and housed in groups of up to four in individually ventilated cages (GM500, Tecniplast, Italy) in environmentally controlled rooms with a twelve-hour light-dark cycle. At E6.5, female mice received new drinking water mixed with dolutegravir (GSK-1349572A; AmBeed, Arlington Heights, Illinois, USA) in 0, 3.5 mg/l, 17.5 mg/l, or 35 mg/l concentrations to achieve 1×, 5×, or 10× clinical concentrations of DTG in serum [14]. Water and DTG-water consumption did not vary between groups and was approximately 5.45 ml/mouse per day.…”
Section: Methodsmentioning
confidence: 99%
“…To test our hypothesis, we administered DTG to CD-1 outbred mice provided with normal (3 mg/kg) or low (0.3 mg/kg) folic acid diet. Pregnant dams were treated with water, human equivalent dose (HED) (1×, 3.5 mg/l) [14] or supratherapeutic (5×, 17.5 mg/l; 10 ×, 35 mg/l) levels of DTG from mouse embryonic day E6.5 to E12.5, which encompasses the entirety of neural tube closure in mice. Dams ( n = 20 per treatment group) were sacrificed at term (E18.5).…”
Section: Introductionmentioning
confidence: 99%
“…The study authors reported that DTG inhibits renal transporter OCT2, resulting in a mild increase in SCr that is reversible [ 27 ]. Eadon et al subsequently reported that other specific biomarkers showed no evidence of renal injury [ 28 ]. Dolutegravir is eliminated (approximately 64%) in feces [ 29 ].…”
Section: Integrase Strand Transfer Inhibitors (Instis)mentioning
confidence: 99%
“…Results confirmed that RAL significantly increases the SCr levels (0.25 mg/dL) compared to control (0.17 mg/dL). The study authors concluded that there were no direct signs of nephrotoxicity and attributed the increase in the SCr level to the direct inhibition of renal OCT2 transporters [ 28 ]. The second trial was a single center, retrospective chart review that assessed SCr and CrCl in newly diagnosed PLWH.…”
Section: Integrase Strand Transfer Inhibitors (Instis)mentioning
confidence: 99%